AROMATERAPI LEMON MENURUNKAN TINGKAT NYERI PADA IBU POSTPARTUM SECTIO CAESAREA - Heru Setyowati, Agnes; Kustriyanti, Dwi; Widiati, Amrih (Akademi Keperawatan Karya Bhakti Nusantara, Magelang, Indonesia, 2025)
Background: Sectio caesarea is an artificial birth method that aims to deliver the baby. This action physically causes pain in the abdominal area due to surgery. Management of this pain can be done through non-pharmacological therapy such as lemon aromatherapy. Objective: To analyze the effect of lemon aromatherapy on pain levels in post-sectio caesarea mothers. Research Method: This type of research is quasi-experimental with pre-test and post-test without control design. The research sample was 30 post-sectio caesarea mothers who were determined using the accidental sampling technique. Intervention was given by giving lemon aromatherapy for 30 minutes. Measurement of pain data using the Numerical Rating Scale. Research data were analyzed using the Wilcoxon test. Results: Giving lemon aromatherapy effectively reduced pain in all research respondents with a p value of 0.000. Conclusion: Lemon aromatherapy therapy can be used as an alternative therapy in handling cases of pain in post-CS mothers.